2020
DOI: 10.3390/ani10091656
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of the Microalga Scenedesmus sp. in Diets for Rainbow Trout, Onchorhynchus mykiss, Juveniles

Abstract: A nutritional study was conducted to evaluate the inclusion of the green microalga Scenedesmus sp. at 5% (SCE-5) as an alternative fishmeal ingredient. This microalga was tested with four replicates during 45 days using isolipidic (18%), isoproteic (48%), and isoenergetic (1.9 MJ kg−1) diets. Fish fed Scenedesmus sp. showed similar growth and feed efficiency parameters as the control group. Regarding the digestive function, the SCE-5 diet enhanced the activity of alkaline pancreatic proteases, whereas it did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…A study revealed that the vacuoles in the liver of juvenile Senegalese sole (Solea senegalensis) disappeared after 90 days of feeding of the macroalga, Ulva ohnoi [76]. On the other hand, the microalga Scenedesmus sp., when included in feeds, did not cause any adverse effects in both the intestine and liver of rainbow trout [77]; here, the alga inclusion was only 5%. Our findings suggest that incorporation of microalgae at 30%, and in particular the double extrusion of microalgae, may have affected the nutrient availability or metabolism of nutrients.…”
Section: Intestinal Healthmentioning
confidence: 59%
“…A study revealed that the vacuoles in the liver of juvenile Senegalese sole (Solea senegalensis) disappeared after 90 days of feeding of the macroalga, Ulva ohnoi [76]. On the other hand, the microalga Scenedesmus sp., when included in feeds, did not cause any adverse effects in both the intestine and liver of rainbow trout [77]; here, the alga inclusion was only 5%. Our findings suggest that incorporation of microalgae at 30%, and in particular the double extrusion of microalgae, may have affected the nutrient availability or metabolism of nutrients.…”
Section: Intestinal Healthmentioning
confidence: 59%
“…The results of the present study are similar to other feeding trial studies in which the authors did not detect any significant effects on growth parameters when FM was partially replaced by different strains of AB in Atlantic salmon diets [30,31], hybrid striped bass diets [32], European seabass [33], and shrimp diets [34], just to mention a few. Although immunology, lipid oxidation, goblet cells, mucus production, and the microbiome were not a focus of this study, other studies that included microalgal biomass in feeds in aquaculture revealed positive results in enhancing immune response [35,36], decreasing nitric oxide [37], increasing goblet cell density in the anterior intestine [38], modulating mucosal immune function, and increasing microbiome diversity indices for microbial communities in the gut of fish fed diets with PUFA-rich microalgae compared with controls [36]. This further supports the potential of marine microalgae as an alternative food source in aquafeeds, either as oil or as biomass.…”
Section: Discussionmentioning
confidence: 91%
“…Evidence from the literature has shown that including certain microorganisms in the diet can improve meat coloration. Skalli et al [68] showed that the inclusion of microalgae Scenedesmus sp. in the diet of rainbow trout significantly improved the fillet yellowness, color saturation, and hue angle.…”
Section: Bacterial Taxa Enriched In the Red Fillet Fishmentioning
confidence: 99%